Association Of Gestational Age And Birth Weight With Neonatal Sepsis In Ulin Hospital Banjarmasin - Andayani, Pudji; Salim, Monica Anggriana; Halim, Pricilia Gunawan; Yunanto, Ari (Fakultas Kedokteran Universitas Lambung Mangkurat, 2023)
Indonesia is ranked 7th in the country with the highest neonatal mortality rate in the world, respectively 60.000 neonatal deaths per year. Neonatal sepsis in one of the major causes of neonatal death. The aim of this study is to find the association of gestational age and birth weight with the incidence of neonatal sepsis in Ulin Hospital Banjarmasin, January-December 2021. This study is a retrospective study with a cross sectional approach at Neonatal Ward, Ulin Hospital Banjarmasin, South Borneo, January to December 2021. The total sample was 200 infants consisting of 100 healthy infants and 100 sepsis infants. The source of gestational age, birth weight, and diagnosis data were taken through patient medical records. The mean gestational age of healthy infant group was 38,45 weeks (all infants were at term) while in septic infant group was 33,59 weeks (70%preterm, 28%at-term, and 2%post-term). The average birth weight of healthy infant group was 3021.24 grams (all infants were normal birth weight) while in septic infant group was 2003,59 grams (25%normal birth weight, 40%low birth weight, 25%very low birth weight, and 10%extremely low birth weight). There were an association of gestational age and birth weight with neonatal sepsis, confidential rate was 95%. (p<0,000 and p<0,000). There were an association of gestational age and birth weight with neonatal sepsis in Ulin Hospital Banjarmasin, January-December 2021.